Rapid identification of a Leptotrichia trevisanii catheter-related bloodstream infection using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Issue 4 (31st August 2015) - Martín-Gutiérrez, Guillermo; Rodríguez, Nancy; Lepe, José Antonio; Parody, Rocío; Torres, María José; Aznar, Javier
Abstract : Introduction: Leptotrichia trevisanii is a large, fusiform, non-sporulating, motile, Gram-negative rod, and is a member of the family Fusobacteriaceae in the phylum Fusobacteria . Although L. trevisanii bacteraemia is extremely rare, severe infections have been reported in immunocompromised patients. Case presentation: We present a case of a 69-year-old woman diagnosed with diffuse large B-cell lymphoma, who suffered a catheter-related bloodstream infection due to L. trevisanii during the post-autologous peripheral blood progenitor-cell transplantation aplasia phase. In this case, rapid identification of the opportunistic pathogen was achieved using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry directly from a blood culture, with correct identification of the micro-organism within 2 h after the blood culture became positive. Conclusion: Rapid identification of this opportunistic pathogen allowed initiation of appropriate antimicrobial therapy, which contributed to a successful clinical outcome for the patient.